HOW ACTIVE PLAY FACILITIES FOSTER PHYSICAL LITERACY ON 5-6 YEARS OLD CHILDREN? LESSON FROM JAMBI, INDONESIA - Librianty, Herwina Dewi (Journal of Early Childhood Education (JECE), 2021)
The purpose of this study was to determine the effect of the availability of active playing facilities on the physical literacy of children aged 5-6 years who are currently undergoing education at ECE (Early Childhood Education) centers in three sub-districts of Jambi City, Jambi Province. This study uses a comparative quantitative approach with ex-post facto techniques. The samples were determined using a convenience sampling technique involving 100 children in five PAUD institutions. Data collection was carried out through direct observation with data analysis using the F test and Tukey test. The results showed that there were differences in the level of physical literacy between groups of children in institutions with the availability of complete active play facilities compared to groups of children in institutions with incomplete availability of active play facilities.